ANALISIS KEMAMPUAN LITERASI PESERTA DIDIK DITINJAU DARI PENALARAN MATEMATIKA - Nasyihah, Fia; Prasetyowati, Dina (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2024)
His research aims to determine students' literacy abilities in terms of mathematical reasoning at SMA Negeri 10 Semarang. The type of research used in this research is qualitative research with test instruments and interviews. The sample population in this research is all students in class X-11 of SMA Negeri 10 Semarang. The data analysis used is data reduction, data presentation, and drawing conclusions. Based on data analysis, it was found that: Students with high mathematical abilities on average carry out the literacy process so that they can understand problems, practice concepts, solve problems, and connect problems with each other, in the reasoning process so that they can analyze conjectures, plan processes, solve problems, and draw conclusions. Furthermore, students who have moderate mathematical abilities can only carry out the literacy process to understand problems and solve problems. These students can only carry out the reasoning process until they reach a guess and do not determine generalizations correctly. Finally, students who have low mathematical abilities on average have literacy skills only to understand the problem and cannot put concepts into practice and students in reasoning only to determine initial guesses and they find it difficult to convey the results of their answers during interviews.